USM TO PAVE NEW COLLABORATIVE PATHWAYS WITH CZECH REPUBLIC UNIVERSITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 22 May 2015 As Universiti Sains Malaysia (USM) establishes itself in its academic standing and rankings, it is also active in pursuing and welcomes collaborations with many other institutions around the world. USM ViceChancellor, Professor Dato’ Dr. Omar Osman highlighted this in delivering his welcoming remarks and presentation on USM to the delegates from the Czech Republic.